Using Problem-Based Learning Models to Improve Students' Critical Thinking Skills - Wenny Sulistya Ningrum; Pratiwi Pujiastuti; Heri Maria Zulfiati (AL-ISHLAH: Jurnal Pendidikan, 2021)
This research aims to enhance critical thinking abilities through the use of problem-based learning in the Social Science Basic Concepts course. The research method used is Classroom Action Research, which is based on the Kemmis and Taggart model. This research was conducted in two cycle, with the researcher serving as a lecturer and observer during each cycle. The subject of the research was elementary school teacher education. The data collected are presented in table format and analyzed quantitatively in a descriptive manner. The findings indicated that implementing the Problem Based Learning model can help students improve their critical thinking abilities. The results of critical thinking observations in cycle 1 were 39% (poor), and the results of critical thinking skills tests improved from 26% (poor) to 54% (fair). Cycle II was conducted using the same model, and the observation results for critical thinking skills increased from 39% (poor) to 78% (good).  The increasing of students pass critical thinking skills tests from 54% (fair) to 91% (good). It can be concluded that using the Problem Based Learning model can help elementary school teacher education students improve their critical thinking skills.